2013
DOI: 10.1166/jnn.2013.7448
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodisperse LuPO<SUB>4</SUB>:Eu<SUP>3+</SUP>/Tb<SUP>3+</SUP> Hollow Nanospheres and Their Luminescence Properties

Abstract: Highly uniform and well-dispersed LuPO4 hollow nanospheres were successfully synthesized via a facile solution-phase method by utilizing the colloidal spheres of Lu(OH)CO3 as a sacrificial template and NH4H2PO4 as a phosphorus source. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed infrared (FT-IR), photoluminescence (PL) spectra, and cathodoluminescence (CL) spectra were employed to characterize the samples. The result indicates that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Polyacrylic acid (PAA) was used as the functionalizing molecule (see the followed procedure in the Experimental section) due to its highly hydrophilic nature, which is appropriate for applications in the biotechnology eld. 14 The FTIR spectrum of the PAA-treated particles exhibited, in addition to the bands found in the spectrum of the nude The FTIR spectra of the particles, before and aer the functionalization process, are shown in Fig.…”
Section: Functionalization and Colloidal Stability Of Eu 3+ -Doped Lumentioning
confidence: 94%
See 2 more Smart Citations
“…Polyacrylic acid (PAA) was used as the functionalizing molecule (see the followed procedure in the Experimental section) due to its highly hydrophilic nature, which is appropriate for applications in the biotechnology eld. 14 The FTIR spectrum of the PAA-treated particles exhibited, in addition to the bands found in the spectrum of the nude The FTIR spectra of the particles, before and aer the functionalization process, are shown in Fig.…”
Section: Functionalization and Colloidal Stability Of Eu 3+ -Doped Lumentioning
confidence: 94%
“…2,5 Many research groups have reported, in the last decade, on the doping of YPO 4 , LaPO 4 , CePO 4 , and GdPO 4 nanoparticles with ions of the f-elements for optoelectronic as well as biotechnological applications. Gao et al 14 reported the synthesis of uniform LuPO 4 hollow spheres using a two-step urea-based process which rendered particles with a diameter of around 300 nm, well above the size of nanometer-scale materials. Gao et al 14 reported the synthesis of uniform LuPO 4 hollow spheres using a two-step urea-based process which rendered particles with a diameter of around 300 nm, well above the size of nanometer-scale materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior study, we reported the synthesis of the monodisperse LuPO 4 hollow spheres by using the Lu(OH)CO 3 precursor spheres as templates through the hydrothermal process [34]. However, to the best of our knowledge, there have been few reports on the synthesis of uniform, well-dispersed micrometre-scaled rare earth-doped LuPO 4 hollow spheres and their corresponding luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researches have reported on the synthesis of YPO 4 [27], LaPO 4 [28], CePO 4 [29] and GdPO 4 [14] micro/nanomaterials. Compared with a great deal of work on other orthophosphate materials, the study on the synthesis of LuPO 4 material has rarely been reported [30][31][32][33][34]. LuPO 4 is an excellent candidate for lanthanide ion substitution because of its favourable physical properties, such as high chemical stability, high melting point, high quantum yield and low toxicity.…”
Section: Introductionmentioning
confidence: 99%